Islamic conquestof the Maghreb from the perspectiveof theFrench Orientalismvision - amrouche, ahmed (Journal of Social Sciences and Humanities, 2020)
French Orientalismwaspreoccupiedwithmany issues in its ratification and itsspecialization and belonged to the colonized peoples and one of these issues was the Islamicconquest of the Maghreb countries considered one of the mostfascinatingsubjects for non-specialist French historianssuch as consuls, Military, administrative and translators, and thosewhotried to highlight the causes of the Islamicconquest of the Maghreb countries, and the motivations of the conquerors, fromtheir point of view, in order to distort the Islamicconquests, , and considerthemwars for spoils and captive, and implanted the ideathat the expansion of Islam in the middle Maghrib territorywas for the purpose of the expansion and discovery of North Africa. Weshould note thatthere are French, specialist or academianhistorianswho are honest about the Islamic expansion in the Maghreb, and this by carrying out research and investigations and by citingtheir exploit and titles. Despite the absence of scientificanalysis in French writingsfollowingpoliticalanalysis mixed withcolonialistideologiesnevertheless, itpresents a historicalmaterial, whichallows the researcher to present a new and differentreading in differentdomains; social, economic, cultural ... The influence of orientalistthoughtisstillpresenttoday, and affects the state of mind of the individual and society. This by the affectation of the Algerian individual and his society by the French culture whichwasestablished by colonialismthroughoutits occupation of Algeria during about a century and a third of a century, the interest of the orientalists to take care of it and its social, economic and cultural effects. In whatfollows, wewillanalyzethroughthis article the French orientalist vision of this question and itshistorical exploitation for the exhaustion of colonialistsupremacy, as well as their exploitation of the writings of Arab origin in theirwritings, and the relationshipbetweenOrientalism, proselytism and colonialism.